THE USE OF “MODIFIED SONG LYRICS” FOR TEACHING WRITING DESCRIPTIVE TEXT TO SEVENTH GRADERS IN SMP NEGERI 7 KOTA MOJOKERTO (RETAIN, 2016)
THE USE OF “MODIFIED SONG LYRICS” FOR TEACHING WRITING DESCRIPTIVE TEXT TO SEVENTH GRADERS IN SMP NEGERI 7 KOTA MOJOKERTO FAJRIN ENA ASMARA PUTRI English Education, Language and Art Faculty, State University of Surabaya fajrinputri@mhs.unesa.ac.id Fauris Zuhri, S.Pd, M.P.d English Education, Language and Art Faculty, State University of Surabaya zuhrifauris@gmail.com Abstrak Dalam bahasa, menulis adalah salah satu keterampilan bahasa setelah mendengarkan, berbicara, dan membaca. Hal ini juga merupakan bagian penting dari komunikasi. Keterampilan menulis yang baik membuat semua orang memberikan dan mengomunikasikan ulasan pesan mereka kepada audiens yang lebih besar daripada melalui tatap muka. Dalam penulisan, penulis mengungkapkan / ide-idenya, pengalaman, dan perasaan untuk tujuan khusus. Hasil penulisan umumnya disebut teks, dan penerima teks disebut pembaca.Dalam proses belajar mengajar, menulis adalah kegiatan untuk mengekspresikan perasaan siswa, pikiran dan ide-ide ke dalam bentuk tertulis. Ketika guru minta ulasan siswa-siswanya untuk menghasilkan ulasan pemikiran mereka, mereka harus berpikir beberapa poin seperti ketertarikan siswa dan bahasa siswa. Penggunaan modifikasi lirik lagu untuk mengajar menulis teks deskriptif antara guru bahasa asing yang dikenal sebagai pengajaran praktis untuk menciptakan konteks penggunaan bahasa otentik di dalam kelas. Media ini penting untuk diajarkan di SMP terutama untuk kelas tujuh. Penelitian ini dirancang sebagai penelitian kualitatif. Subyek penelitian ini adalah siswa kelas tujuh SMPN 7 Mojokerto. Data yang diperoleh dalam penelitian ini berasal dari checklist observasi, penugasan siswa, dan angket. Hasil Data disajikan secara deskriptif. Proses pembelajaran menulis teks deskriptif dengan modifikasi lirik lagu mulai dari melakukan pengamatan. Kemudian, guru mengajar teks deskriptif melalui modifikasi lirik lagu dalam dua pertemuan. Kata Kunci: Keterampilan menulis, pengajaran menulis, teks deskriptif, modifikasi lirik lagu Abstract In language, writing is one of the language skills after listening, speaking, and reading. It is also an important part of communication. Good writing skill makes everyone deliver and communicate their message to the audience larger than through face-to-face. In writing, a writer expresses his/her ideas, experience, and feeling for a special purpose. The result of writing is generally called text, and the recipient of text is called a reader. In teaching learning process, writing is an activity to express the students’ feelings, thoughts and ideas into written forms. When the teacher asks their students to produce their thinking, they have to think some points such as the student’s interest and languages. The use of modified song lyrics to teach writing descriptive text which is well known among foreign language teachers as a practical teaching to create the context of authentic language use in the classroom. This media is important to be taught in Junior High School especially seventh graders.This research was designed as a qualitative research. The subject of the study was the seventh graders of SMPN 7 Kota Mojokerto. The data gained in this research were from observation checklist, students’ assignment, and questionnaire. The results of the data were presented descriptively. The process of teaching writing descriptive text by modified song lyrics started from doing an observation. Then, the teacher taught descriptive text trough modified song lyrics in two meeting.From this research, it showed that the implementation of modified song lyrics for teaching writing in descriptive text and showed good response towards students. In conclusion, modified song lyrics can be implemented to teach writing in descriptive text to seventh graders because it helps them to be more understand, enjoy and happy to learn descriptive text in writing, with smallest help from the teacher. Keywords: Writing skill, teaching writing, descriptive text, modified song lyrics